Treatment Strategies Demonstration of the Omnibus Law in a Democratic Policing Perspective - Wijaya, Fabian Condo; Muriman S, Chairul; Handayani, Riska S. (Journal of Social Research, 2023)
This research aims to analyze the handling of omnibus law demonstrations using a democratic policing approach. Democratic Policing (Democratic Policing) should be a consequence of the Polri reform agenda, a reformative agenda regarding the posture of the Polri in the political system of the Republic of Indonesia, covering the culture of Polri personnel in the implementation of national security. This research is qualitative. The results of this research explain the efforts that have been made by Polda Metro Jaya in handling the Omnibuslaw demonstration, namely; a) Pre-emptive efforts to provide advice to protesters about good demonstration procedures and inform the relevant agencies that are the target points for demonstrations and/or demonstrations, b) preventive efforts have been carried out by the Police in carrying out their duties by fixed procedures (Protap). This is intended so that the police, both individuals and units, in taking action are not seen as excessive by the public.